Edge of seventeen - Fremon, Kelly; Brooks, James L.; Sakai, Richard; Ansell, Julie (Film producer); Steinfeld, Hailee; Harrelson, Woody; Sedgwick, Kyra; Richardson, Haley Lu; Jenner, Blake, 1992-; Szeto, Hayden, 1985-; Emmett, Doug; Wadmore-Smith, Tracey; et al. (Universal City, CA Universal Pictures Home Entertainment, 2017)
High-school life gets even more unbearable for Nadine when her best friend, Krista, starts dating her older brother.
Title from container.
Originally produced as a motion picture in 2016.
Originally issued as part of a Blu-ray + DVD combo pack.
Wide screen (1.85:1).
Bonus features: gag reel; deleted scenes.
Director of photography, Doug Emmett ; editor, Tracey Wadmore-Smith ; music, Atli Orvarsson.
Keywords: High school students -- Drama; Best friends -- Drama; Friendship -- Drama; Siblings -- Drama; Dating (Social customs) -- Drama; Blu-ray discs; Blu-ray discs -- Spanish subtitles; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Comedy films; Coming-of-age films; Drama; Feature films; Fiction films